2020
DOI: 10.1111/gcb.15000
|View full text |Cite
|
Sign up to set email alerts
|

Climate change fingerprints in recent European plant phenology

Abstract: A paper published in Global Change Biology in 2006 revealed that phenological responses in 1971–2000 matched the warming pattern in Europe, but a lack of chilling and adaptation in farming may have reversed these findings. Therefore, for 1951–2018 in a corresponding data set, we determined changes as linear trends and analysed their variation by plant traits/groups, across season and time as well as their attribution to warming following IPCC methodology. Although spring and summer phases in wild plants advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
148
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(189 citation statements)
references
References 60 publications
18
148
0
Order By: Relevance
“…Numerous methods have been utilized to elucidate the intensity of the effect of climate change on agronomic cereal crops. The methods include analysis of satellite images on vegetation greenness, measurement of net primary production with Normalized Difference Vegetation Index (NDVI), and particularly, determination of temporal and spatial variations in phenological seasonality 26,79,[110][111][112][113][114][115] . The data on stages and phases of cereal crop phenology and climate meteorological data are collected from phenological networks or through designated observation stations.…”
Section: Role Of Phenological Stages and Phases In Cereal Crop Grain mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous methods have been utilized to elucidate the intensity of the effect of climate change on agronomic cereal crops. The methods include analysis of satellite images on vegetation greenness, measurement of net primary production with Normalized Difference Vegetation Index (NDVI), and particularly, determination of temporal and spatial variations in phenological seasonality 26,79,[110][111][112][113][114][115] . The data on stages and phases of cereal crop phenology and climate meteorological data are collected from phenological networks or through designated observation stations.…”
Section: Role Of Phenological Stages and Phases In Cereal Crop Grain mentioning
confidence: 99%
“…Thus the asymmetric and opposing response of phenology to daytime and night-time was studied by Wang et al 82 and concluded that T max and night-time T min had opposite effects on the timing of start of the season, delayed end of the season and prolonged length of growing season. Furthermore, several earlier studies documented that the intensity of the response of phenological stages and phases of agricultural crops to warming trend is variable at spatio-temporal scales 79 , 83 , 84 . Phenology is well known climate change indicator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional cues associated with spring phenological events for some species include autumn temperature (Heide, 2003;Sparks et al, 2020), day length (Heide, 1993a;Heide, 1993b;Körner and Basler, 2010;Basler and Körner, 2012;Laube et al, 2014a), light quality (Brelsford and Robson, 2018), air humidity (Düring, 1979;Laube et al, 2014b;Zipf and Primack, 2017), or nutrient availability (Jochner et al, 2013a). Under natural in situ conditions it is difficult to disentangle these multiple and often co-varying environmental factors (e.g., Piao et al, 2019;Menzel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the annual cycle of plants are closely linked to the seasonal course of temperature, light and water supply, among other factors, and phenological observations constitute direct evidence of plants’ responses to these changes. With these regards, phenological data contribute tangibly to our understanding of global change biology (Menzel 2000 , 2002 ; Parmesan and Yohe 2003 ; Piao et al 2019 ; Menzel et al 2020 ). In Europe, the plant phenological data have demonstrated an average advance of spring/summer 2.5 days per decade between the years 1971 and 2000, in accordance with instrumentally observed warming (Menzel et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%